Artificial Intelligence and the Future of Healthcare in Pakistan: Opportunities and Challenges - Rehman Siddiqui; Atif Zafar; Saad Ahmed Qazi (Journal of the Pakistan Medical Association, 2023)
Artificial Intelligence (AI) is rapidly transforming healthcare across the world. However, in Pakistan, the use of AI in healthcare is still in its early stages. AI has the potential to improve healthcare delivery, particularly in low and middle-income countries (LMICs).1,2 In the Pakistani context, AI presents an opportunity to address the scarcity of healthcare workforce and resources in Pakistan.3 In particular, AI can help bridge the healthcare gap by providing services to underserved populations in rural and remote areas of the country.4 Continue...